Olympic Doping, Transparency, and the Therapeutic Exemption Process - Luke Cox (Diagoras, 2017)
Within anti-doping policy, the Therapeutic Use Exemption policy enables athletes with a range of medical conditions to compete within elite sport even after receiving prohibited medication substances or methods. It has been claimed, however, that the policy is being misused as a means to enhancing performance in healthy athletes, or athletes who do not suffer from a relevant pathological condition. To counter misuse of TUEs, it has claimed that the data captured in the TUE process should be transparent, even though this would reveal medical information concerning the athlete that would normally be thought of as private. There are further concerns regarding the sharing of medical data within sports organisations, between medical professionals and performance directors or coaches. We critically explore the TUE process, and argue against proposals for a transparent TUE policy on grounds of privacy and concerns for athlete welfare .We conclude that the notion of sports integrity, the threat of doping, and the extension of anti-doping policy, need to be considered within a broader context that also concerns the goals of sports medicine and athlete welfare.